The Invention of New Love in Psychoanalysis - Tomšič, Samo (Filozofski vestnik, 2011)
The article discusses the relation between psychoanalysis and philosophy from the perspective of love. But psychoanalysis demonstrates that this love is possible only based on a return to the origins of psychoanalysis where a new modality, or a new image of love is invented in connection with transference. As in philosophical love for knowledge, transference love presupposes a “ready made” operative knowledge which serves the analyst in the interpretation of a double supposition: besides knowledge, it also presupposes its subject: the subject supposed to know. The problematic of transference love is then linked to Lacan's final elaborations of the unconscious in relation to the real. The passage from transference unconscious to the real unconscious abolishes the love for knowledge, but the inverse movement provides ground for a “new love” to emerge, love as invention. The two modalities of love are discussed in connection with Lacan's formulas of sexuation and with the question of the inexistence of the sexual relation.